Indian Country Diaries. Compare : spiritual health - Cornsilk, Carol; Adanvdo Vision (Firm); Native American Public Telecommunications, Inc.; Vision Maker Media (Lincoln, NE : Vision Maker Media, 2005)
Indian Country Diaries goes inside modern Native American communities to reveal a diverse people working to revitalize their culture while improving the social, physical, and spiritual health of their people. This special feature discusses Cherokee food and health.
Title from resource description page (viewed May 24, 2016).
In English.
Keywords: Indians of North America; Cherokee Indians -- Social conditions; Cherokee Indians -- North Carolina -- Social conditions; Cherokee -- Conditions sociales; Cherokee -- Caroline du Nord -- Conditions sociales; Cherokee Indians -- Social conditions; Indians of North America; North Carolina; documentary film; Documentary films; Documentary films; Documentaires